Antioxidant Activity Assay of Black Turmeric (C. Caesia) Water and Ethanol Extracted Using DPPH - Kartini, Sri; Susanti, Pratiwi; Marshanda, Isty Maulia; Pratiwi, Denia; Mardhiyani, Dini; Hendrika, Yan (Poltekkes Kemenkes Riau, 2023)
Antioxidants are compounds that provide electrons; they function by donating an electron to oxidizing compounds, thereby inhibiting the activity of these oxidants. The objective of this study is to ascertain the presence of secondary metabolites and evaluate the antioxidant properties of water and methanol extracts obtained from black turmeric (C. caesia). The determination of antioxidant activity was conducted using the DPPH method with a microplate reader at a wavelength of 520 nm, by calculating the IC50 value. The research findings indicate that both water and methanol extracts contain flavonoids, saponins, and tannins. The antioxidant activity of the water extract measured at 392.47 ± 46.38 ppm (weaker), the methanol extract displayed a higher activity at 69.66 ± 2.91 ppm (strong), and Vitamin C exhibited very strong activity at 3.98 ± 0.26 ppm.